Consumer adoption of online food delivery ordering (OFDO) services in Pakistan: The impact of the COVID-19 pandemic situation - Saqib Ali; Nadeem Khalid; Hafiz Muhammad Usama Javed; Dewan Md Zahurul Islam (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Evolving internet technology has brought about changes in consumer lifestyle and increased online shopping. Grounded in the theory of technology readiness (TR), this study aims to examine the effect of factors such as optimism, innovativeness, insecurity, and discomfort that may motivate consumers' adoption intentions towards online food delivery ordering (OFDO) services. Additionally, this study intends to investigate the moderating role of situational influences (COVID-19) in affecting such an online behavior. By using survey methods, a total of 439 usable responses were gathered through an online survey. Data were analyzed by using Partial least square (PLS) and multigroup analysis (MGA) techniques. The results revealed that optimism and innovativeness have positive influences on adoption intentions while insecurity and discomfort have negative influences on adoption intentions in the use of OFDO services. The results also supported the moderating role of situational influences such as the COVID-19 pandemic. Furthermore, the PLS-MGA results indicate that the effects of optimism and innovativeness are stronger in demographic variables, i.e., young, male, high income, high education, etc. On the contrary, the effects of insecurity and discomfort are stronger for the opposite, i.e., elder, female, low income, low education, etc. Finally, this paper depicts remarkable insights for researchers, practitioners, service providers, and marketers.
Keywords: 650; online food delivery ordering (OFDO) services; situational influences COVID-19; technology readiness (TR) model